Mitigating the severity of child homelessness in the UK: a global mixed-methods systematic review. (November 2021) - Sarkar, Kaushik; Rosenthal, Diana Margot; Martinez, Daniela Cossio; Shrestha, Arunima; Acquilla, Sushma; Svirydzenka, Nadzeya; Heys, Michelle; Ucci, Marcella; Lorgelly, Paula; Raghavan, Raghu; Aldridge, Rob; Lakhanpaul, Monica; et al.
Abstract: Background: In 2019, 585 000 children in England were homeless or at risk of becoming homeless. The pressure of the COVID-19 pandemic on the health-care delivery system has amplified the inequalities faced by marginalised children. Although the UK has had a series of successful health sector reforms, few have designed or implemented strategies that target reach, access, and use of public health services for marginalised children. This project aims to identify such strategies by exploring solutions used in low-income and middle-income countries (LMICs), through reverse-innovation. Methods: We undertook a systematic review of the literature published in English from PubMed, MEDLINE, and SCOPUS between Jan 1, 2010, and March 31, 2021. We explored the literature focusing on policy, strategy, intervention, and services, using keywords and Medical Subject Headings corresponding to the target population, and medical, health, and nutrition services including preventive and immunisation services, and outcomes. Our target population included homeless and marginalised children. We defined marginality in terms of social distances following Braun and Gatzweiler (2013). We included in our search homelessness, temporary accommodation (eg, makeshift accommodation, emergency shelter, and feral), the conditions that put a child at risk of homelessness (eg, war, battle, conflict, refugee, displaced, and migrant), and the general conditions of social distances (eg, poverty, and financial catastrophe) that do not belong to discrimination. We used the Arksey O'Malley framework with Levene's extension in the aforementioned databases and Google Scholar to improve inclusivity. The primary outcomes included access, coverage, and utilisation of child health and nutrition services. The impact measurements included morbidity, mortality, and economic outcomes (return on investment, cost, and efficiency). We applied natural language processing for thematic analysis of qualitative evidence. The analysis was assisted by Python (v3.7.12). Findings: We found 53 final articles (47 quantitative and six qualitative) from LMICs. Community-focused and financial interventions were successful in different settings. Financial interventions such as user-fee removal increased health care and service use between 15–309%. Cash transfers increased immunisation coverage, financial security, and nutrition. Mobile health services and the individualised tactics of community midwives and volunteers improved the coverage and use of child health and nutrition services. Community-based savings groups, user-fee removal, and cash transfer policies improved access and utilisation. mHealth applications and capacity building of health workforce increased coverage and quality of these services and improved clinic attendance. Interpretation: UK policy makers could adapt and adopt targeted and conditional cash transfer policies to provide greater financial security to homeless families and make child health care more affordable and inclusive. Volunteer and mobile-clinic-based community services would increase access and use of these services in the COVID-19 recovery phase. Our review may have missed matured strategies published before 2010. We were unable to estimate a pooled effect. Funding: ESRC, UK Research and Innovation rapid response COVID 19.